PENGARUH PENGAWASAN MANDOR TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. TRI BAKTI SARIMAS ESTATE SEI. KUNYIT KUANTAN SINGINGI - Panjaitam, Karolina; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the effect foreman supervision on employee productivity at PT. Tri Bakti Sarimas Estate Sei. Turmeric Kuantan Singingi. Supervision foreman as the independent variable (X). While employee productivity as the dependent variable (Y). This study was conducted on all employees of PT. Tri Bakti Sarimas Estate Sei. Turmeric Kuantan Singingi many as 73 people.Data obtained from questionnaires and subsequently processed to then be tested using statistical analysis as a simple linear regression analysis, t test, and correlation analysis and determination using SPSS 20.The results showed that the results of the t test of hypothesis testing thitung2,121> ttabel1,994. This shows that the supervision of the foreman effect on employee productivity. The amount of influence foreman supervision on employee productivity padaPT. Tri Bakti Sarimas Estate Sei. Turmeric Kuantan Singingi59,6%.Keywords: Monitoring Overseer and Employee Productivity PT. Tri Bakti Sarimas Estate Sei. Turmeric Kuantan Singingi.